COVID-19: Current Challenges and Future Perspectives - Leggat, Peter; Frean, John; Blumberg, Lucille (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
On March 11, 2020, the World Health Organization declared COVID-19 a global pandemic and the disease now affects nearly every country and region. Caused by SARS-CoV-2, COVID-19 presents significant challenges to health systems and public health in both hemispheres as well as to the economies of each country. The morbidity and mortality due to infections caused by SARS-CoV-2 have been significant despite the short duration since its discovery and initially overwhelmed many hospitals and clinics. It influences everyone, and countermeasures have been dramatic in their impact on employment, social systems, and mental health. This Special Issue provides an avenue for authors from various disciplines to provide feedback on our responses and preparedness to COVID-19 globally as well as to disseminate critical information about the SARS-CoV-2 virus and the associated COVID-19 pandemic. It consists of 22 peer-reviewed papers that cover worldwide perspectives encompasses the following: Original articles about COVID-19 (including epidemiology, modelling, clinical data, treatment, prevention, countermeasures, impacts on tropical regions, response, and preparedness);Original articles about SARS-CoV-2 (microbiology, virology, transmission, pathology, and vaccinology);Perspectives about COVID-19 and SARS-CoV-2 (comparisons with past coronavirus outbreaks, impactful local initiatives, novel responses, and commentaries);Reviews on COVID-19 (based on systematic and narrative reviews);and Innovations (vaccine development, drug trials, and original countermeasures).